DENYING AND DEFLECTING THE RACISM OF EMPIRE: THE TROPE OF THE ‘MALEVOLENT NATIVE’ IN THE WRITINGS OF THE COLONIAL FUNCTIONARY AND AUTHOR HUGH CLIFFORD - Noor, Farish A (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2023)
Hugh Charles Clifford (1866-1941) was a colonial functionary who served in various capacities in British Malaya, notably in the kingdom of Pahang (as colonial agent, 1887-1888; Superintendent (1889) and Resident (1896-1900, 1901-1903). Apart from his duties as a colonial administrator, Clifford was also the author of numerous works of fiction that were set in the kingdom and was thus an active contributor to the colonial imaginary. This paper looks at the fictional works of Hugh Clifford. It focuses on one specific theme that recurs repeatedly in several of his works, which is the notion that the aboriginal and other Asiatic communities of the Malay Peninsula were living under the overlordship of the Malays. That a British colonial functionary like Clifford could have foregrounded such a theme while seemingly unaware of his role and subject-position as a functionary of the British Empire is telling in many respects. In many ways, the fictional works of Clifford can be read as a systematic and sustained effort to deny and deflect the racism at the heart of racialized colonial capitalism then, which served as the basis of British imperial rule across Asia and Africa.